2011
DOI: 10.4081/reumatismo.2004.169
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and risk factors in osteoarthritis: literature review data from “OASIS” study

Abstract: Ostheoarthritis (OA) is a social disease characterized by pain, inflammation and stiffness due to an involvement of articular cartilage, soft tissues and bone.OA is the most common rheumatic disease, every age can be affected but prevalence increases dramatically with age with a greater incidence in subjects between 40 and 50 years of age. Hip OA has an important correlation with weight, genetic factors, sex, previous traumas, occupational factors and age. People older than 35 have a prevalence of Hip OA of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 96 publications
2
23
0
1
Order By: Relevance
“…The data of the Osteoarthritis Southern Italy Study (OASIS) involving 1782 patients in Italy demonstrated that hip OA had an important correlation with weight, genetic factors, sex, previous traumas, occupational factors, and age. Knee OA had a great correlation with weight, lifestyle (sedentary lifestyle, cultural or religious aspects of life), and physical activity (17). Similar results were obtained assessing the data of a case-control study among 101 women in Japan, and later these results were compared to the fi ndings of study in carried out in Britain.…”
Section: Etiology and Risk Factorssupporting
confidence: 70%
“…The data of the Osteoarthritis Southern Italy Study (OASIS) involving 1782 patients in Italy demonstrated that hip OA had an important correlation with weight, genetic factors, sex, previous traumas, occupational factors, and age. Knee OA had a great correlation with weight, lifestyle (sedentary lifestyle, cultural or religious aspects of life), and physical activity (17). Similar results were obtained assessing the data of a case-control study among 101 women in Japan, and later these results were compared to the fi ndings of study in carried out in Britain.…”
Section: Etiology and Risk Factorssupporting
confidence: 70%
“…OA is among the most prevalent diseases affecting adults and a major contributor to physical disability, morbidity, and utilization of health care resources worldwide[2-5]. In patients with severe knee OA who have failed conservative treatments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA) is the most common type of arthritis found worldwide especially in the elderly [7] It is a disease characterized by pain and inflammation due to the involvement of the articular cartilage, soft tissues and bone [8] . Osteoarthritis is the single most common cause of disability in older adults [9] Three major physical impairments, such as knee pain, stiffness, and decreased quadriceps strength, are highly associated with a knee OA and are believed to contribute to physical disability and progression of the disease [26][27][28] As the quadriceps muscle plays the role of shock absorber, a weakness of this muscle decreases the joint protection resulting in greater stress and overload on the knee [25] .…”
Section: Resultsmentioning
confidence: 99%
“…With the population ageing, the prevalence of OA is increasing, and its consequences have a significant impact on the society. 7 It is a disease characterized by pain and inflammation due to the involvement of the articular cartilage, soft tissues and bone [8] Osteoarthritis is the single most common cause of disability in older adults [9] The 2010 Global Burden of Disease Study reports that the burden of musculoskeletal disorders is much larger than estimated in previous assessments and accounts for 6.8% of DALYs % to 15% of all adults aged over 60 have some degree of OA, with prevalence higher among women than men.4 [11] . The prevalence of OA is increasing due to population ageing and an increase in related factors such as obesity.…”
Section: Introductionmentioning
confidence: 99%